COMP-09. HFE EXPRESSION ALTERS OUTCOMES IN BRAIN TUMORS. (5th November 2018) - Nesterova, Darya; Lee, Sang; Stetson, Lindsay; Lathia, Justin; Rubin, Joshua; Waite, Kristin; Berens, Michael; Connor, James
Abstract: Iron homeostasis is essential for cellular energy production particularly in rapidly dividing cells. The HFE protein is critical for regulating cellular iron uptake. To explore the impact of HFE expression in glioblastoma (GBM) and other brain tumors, we utilized TCGA GBM and GBMLGG databases from GlioVis. Within the GBMLGG database which includes lower grade tumors, high expression of HFE was associated with significantly poorer survival. In GBM patients with high HFE expression survival was also significantly worse compared to low HFE expression. There was a strong positive correlation between high HFE expression and tumor grade, with the highest expression in GBM. HFE expression was also correlated to GBM subtype. The lowest expression was in the proneural subtype and the highest in the mesenchymal subtype consistent again with high expression associated with worse prognosis. Normally MGMT methylation is associated with better outcome. However, when combined with high HFE expression there is a significant reduction in survival time (12.9 vs. 20.8 months). To identify the possible molecular basis for these survival differences, we interrogated the reverse phase protein array data (RPPA) for TCGA datasets and discovered a correlation between high HFE expression and expression of a number of proteins. Annexin-1 has the highest correlation of expression with HFE. This protein plays a critical role in innate immune response through the generation of proinflammatory mediators and modulates migration and the phagocytotic ability of neutrophils and macrophages. We have previously shown that mutations in the HFE protein alter macrophage phenotype. Mutations in the HFE gene, the most common autosomal recessive polymorphism found in Caucasians, reportedly impacts the progression of a number of diseases including GBMs. This study identifies HFE as a negative modulator of outcome in brain tumors.